Quality job indicators for individuals with learning disabilities. (3rd April 2019) - Brendle, Janna L.; Lock, Robin H.; Smith, Lisa A.
Abstract: This study identifies the quality job indicators and employer training required to provide appropriate support for students with learning disabilities (LD) to obtain and maintain employment. A consortium of collaborators was established from a university and state workforce commission grant project, a school district and 55 employers. Employers were trained to implement the quality indicators identified in literature found to support students with LD in paid employment while attending high school. The methodology consisted of gathering qualitative data from employer surveys and interviews reporting experiences and examining data results. Participants included 56 students with LD placed with 55 employers who had been trained in implementing the identified quality job indicators. Fourteen of the 21 quality job indicators were reported to be implemented by at least 90% of the employers. The quality indicators implemented are related to time expectations, on-the-job training, retraining, problem solving, supervision, verbal and written communication, flexible scheduling, breaks and positive reinforcement. The employers reported training in the use of the quality job indicators was effective in providing individuals with LD positive support in the workplace.